Growth Performance of Pangasius sp Fed Different Types of Diets Formulated from Varieties Fish Meal Sources - Khamsiah Ahmad; Aras Syazili; Surahman Surahman; Mutmainnah Mutmainnah (Universitas Khairun, 2022)
Pangasius sp is an introductory species that is widely distributed in freshwater regions in Indonesia since the 1990s and it was initiatively reared at the beginning of 2011 using a floating net cage in Lake Ngade, Ternate. Even though it has benefited economically, there is still a lack of information on its biological and ecological aspects. Growth and survival rate are two main factors that should be known to develop Pangasius aquaculture. The study aims to understand the growth and survival rate of Pangasius by mixing different fish meals into dietary. 120 Pangasius fingerlings were placed into 12 tanks. Diet was formulated using Pearson’s square method. Three different protein fish meal sources were mixed into feed formulation namely flying fish meal, Nile meal, and eel meal. Commercial feed was used as control. Filling Randomized Design (FRD) was applied with the experimental set-up of the treatments. The results show that feed stability in water ranges from 2'23